Schopenhauer’s Pessimism And Nietzsche’s Optimism In Will Humans : Islamic Perspective as Middle way - Anggraini, Oci Anggraini; Sa'adah Mardliyati; Elvira Purnamasari (UIN Sunan Kalijaga Yogyakarta, 2025)
The competitive life of modern humans is often colored by the pressure to achieve success, thus giving rise to two basic attitudes, namely pessimism and optimism that come from human will. This study aims to explore how Schopenhauer and Nietzsche's perspectives on human will relate to pessimistic and optimistic attitudes in the context of competitive modern life. The research question posed is how these two philosophical views can be integrated with the Islamic perspective to find a balance between the two. The method used is descriptive qualitative research through literature study, which uses the method of interpretation and dialogical analysis of the works of both philosophers as well as Islamic texts. The results of the study show that Schopenhauer sees the will as a source of suffering that produces pessimism, while Nietzsche emphasizes the will to power as a driver of optimism and growth. The Islamic perspective offers a middle way by emphasizing the importance of ikhtiar and tawakal, which allows individuals to accept uncertainty while remaining optimistic. By combining these two views, this study highlights how the balance between pessimism and optimism can help individuals face the challenges of modern life and reach their maximum potential.